2021
DOI: 10.1021/acschemneuro.1c00687
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of 3D-FLAIR MRI in Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Background: Three-dimensional fluid-attenuated inversion recovery sequence magnetic resonance imaging (3D-FLAIR MRI) has been used in the diagnosis of inner ear diseases. However, the relevance of 3D-FLAIR MRI appearances with multiple features and prognosis of patients with idiopathic sudden sensorineural hearing loss (ISSNHL) remains unclear. Methods: This study was a retrospective trial. We recruited 1300 patients with unilateral ISSNHL hospitalized from May 2017 to January 2019. They were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Considering the correlation between 3D-FLAIR performance and the prognosis of SSNHL, previous studies had shown some disagreements due to the inconsistencies in examination, diagnosis, and treatment [Berrettini et al, 2013;Lee et al, 2016;Conte et al, 2022;Wang et al, 2022]. In our study, the patients with positive MR findings had a higher incidence of abnormal OAEs and suffered from severe to profound HL.…”
Section: Discussionmentioning
confidence: 49%
“…Considering the correlation between 3D-FLAIR performance and the prognosis of SSNHL, previous studies had shown some disagreements due to the inconsistencies in examination, diagnosis, and treatment [Berrettini et al, 2013;Lee et al, 2016;Conte et al, 2022;Wang et al, 2022]. In our study, the patients with positive MR findings had a higher incidence of abnormal OAEs and suffered from severe to profound HL.…”
Section: Discussionmentioning
confidence: 49%
“…Te results indicate that the brain functional network of patients with sudden SHL tended to change to a regular network, and the ability of information integration was enhanced, while the ability of separation and transmission was weakened. All the above results confrm to some extent that the connection between auditory brain areas and language and vision-related functional areas was weakened in patients with burst SHL, and their language perception and understanding ability were decreased [27].…”
Section: Discussionmentioning
confidence: 52%
“…Through clinical experience and literature study, we found that audiological examination, vestibular function and imaging tests are closely related to the prognosis of SSNHL. [9][10][11]…”
Section: Main Outcome Measuresmentioning
confidence: 99%